Comparing Depressive Symptoms, Emotional Exhaustion, and Sleep Disturbances in Self-Employed and Employed Workers: Application of Approximate Bayesian Measurement Invariance - Bergman, Louise E.; Bernhard-Oettel, Claudia; Bujacz, Aleksandra; Leineweber, Constanze; Toivanen, Susanna (Frontiers in Psychology, 2021)
Studies investigating differences in mental health problems between self-employed and employed workers have provided contradictory results. Many of these studies utilize validated for employed workers, without collecting validity evidence for making comparisons with self-employed. The aim of this study was 1) to collect validity evidence for three different scales depressive symptoms, emotional exhaustion and sleep disturbances for employed workers, self-employed workers and combinators, and 2) to test if these groups differed. We first conducted approximate measurement invariance analysis and found that all scales were invariant at the scalar level. Self-employed workers had least mental health problems and employed workers had most, but differences were small. Though we found the scales invariant, we do not find them optimal for comparison of means. To be more precise in describing differences between groups, we recommend using clinical cut-offs, or scales developed with the specific purpose of assessing mental health problems at work.